Boosting Tenth Graders' Descriptive Writing Skills Through Picture-Based Teaching at SMKN 41 South Jakarta - Kusumadewi, Hermariyanti; Puspitorini, Ferawaty (Universitas Pamulang, 2025)
The purpose of this study is to determine the effect of using pictures as teaching media on students’ descriptive text writing skills in the tenth grade at SMK Negeri 41 South Jakarta. The research employed a quantitative method, specifically a real experimental design. The population of this study consisted of tenth-grade students at SMK Negeri 41, with 32 students in the X DKV-1 class serving as the experimental group and 32 students in the X DKV-2 class as the control group. Based on the research findings, the experimental class had a mean score of 80.3, a median of 86, a mode of 82.5, a variance of 6.24, and a standard deviation of 39.051. Meanwhile, the control class recorded a mean score of 75.26, a median of 76, a mode of 78.3, a variance of 5.72, and a standard deviation of 32.827. The results indicate that the t-test value observed was higher than the t-table value. This confirms that the alternative hypothesis was accepted, and the null hypothesis was rejected. It can be concluded that there is a significant effect of using pictures as media in the learning process. The use of pictures significantly improves the writing skills and creativity of students in English descriptive text in the X grade at SMK Negeri 41 South Jakarta.